Natesto™, a novel testosterone nasal gel, normalizes androgen levels in hypogonadal men. (22nd December 2015) - Rogol, A. D.; Tkachenko, N.; Bryson, N.
Summary: Advantages of testosterone nasal gel include ease of administration, low dose, and no risk of secondary transference. The efficacy and safety of testosterone nasal gel was evaluated in hypogonadal males. The ninety‐day, randomized, open‐label, dose‐ranging study, included potential dose titration and sequential safety extensions to 1 year. At 39 US outpatient sites, 306 men (mean age 54.4 years) with two fasting morning total serum testosterone levels <300 ng/dL were randomized ( n  = 228, b.i.d. dosing; n  = 78, t.i.d. dosing). Natesto ™ Testosterone Nasal Gel was self‐administered, using a multiple‐dose dispenser, as two or three daily doses (5.5 mg per nostril, 11.0 mg single dose). Total daily doses were 22 mg or 33 mg. The primary endpoint was the Percentage of patients with Day‐90 serum total testosterone average concentration ( C avg ) value within the eugonadal range (≥300 ng/dL, ≤1050 ng/dL). At Day 90, 200/273 subjects (73%; 95% CI 68, 79) in the intent‐to‐treat (ITT) population and 180/237 subjects (76%; 71, 81) in the per‐protocol (PP) population were in the normal range. Also, in the normal range were 68% (61, 74) of ITT subjects and 70% (63, 77) of PP subjects in the titration arm, as well as, 90% (83, 97) of ITT subjects and 91% (84, 98) of PP subjects in the fixed‐dose arm. Natesto ™ 11 mg b.i.d. or 11 mg t.i.d. restores normal serum total testosterone levels in most hypogonadal men. Erectile function, mood, body composition, and bone mineral density improved from baseline. Treatment was well tolerated; adverse event rates were low. Adverse event discontinuation rates were 2.1% (b.i.d.) and 3.7% (t.i.d.). This study lacked a placebo or an active comparator control which limited the ability to adequately assess some measures.